Preoperative dobutamine stress echocardiography in patients undergoing orthotopic liver transplantation. Issue 7 (17th July 2018) - Patel, Krishna K.; Young, Laura; Carey, William; Kohn, Kathryn A.; Grimm, Richard A.; Rodriguez, L. Leonardo; Griffin, Brian P.; Desai, Milind Y.
Abstract : Background: Coronary artery disease (CAD) is associated with increased mortality in patients who undergo orthotopic liver transplantation (OLT). Chronic vasodilatory state and poor exercise tolerance in patients with end‐stage liver disease make dobutamine stress echocardiography (DSE) preferred for preoperative evaluation of CAD prior to OLT. We studied the incidence of positive DSE results and the association between DSE results and perioperative and longer‐term events. Hypothesis: DSE results pre‐OLT will predict short and long term outcomes. Methods: We studied 460 patients who underwent DSE within 1 year prior to OLT between 2004 and 2011. Primary events included death and MI at 30 days post‐OLT. We also recorded longer‐term deaths. Results: Four patients (0.9%) had an ischemic response to DSE, 360 (78%) were normal, and 96 (21%) were nondiagnostic. Fourteen patients (3%) had a primary event at 30 days following OLT (13 deaths and 1 NSTEMI), and there were 108 (24%) deaths at 4.6±2 years of follow‐up. No patient with ischemia on DSE had a 30‐day event. The accuracy, sensitivity, specificity, and positive and negative predictive values of DSE that was not normal (ie, ischemic or nondiagnostic response) to predict 30‐day post‐OLT events were 76%, 14%, 78%, 2%, and 97%, respectively. On Cox survival analysis, only baseline left ventricular ejection fraction (HR: 0.90, 95% CI: 0.85–0.96, P  < 0.001) was associated with longer‐term deaths. Conclusions: Patients undergoing pre‐OLT DSE have very low incidence of an ischemic response on DSE, and it has no association with 30‐day events.